Cryptocurrency-Based Financial Science Strategy In World Influence Using Causal Diagram And Machine Learning: English - Gilang Pratama (Quantitative Economics and Management Studies, 2023)
Cryptocurrency is a digital currency that can be used for transaction on an international scale and as an investment. The potential provided by cryptocurrency in the development of the digital economy in the world has become a special attraction for individuals, organizations, and government. Blockchain system that underlies cryptocurrencies has worked flawlessly in both the financial and non-financial worlds. This study uses Basic Risk Management Ishikawa Diagram and evaluated by ARIMA predictive algorithm in determining cause and effect of the development of cryptocurrencies. It was found that the development of cryptocurrency is very influential by the state of the world, especially countries that have great influence such as USA. USA inflation have a big influence, and the model can be used as a basis for a country's government in observing.